Health conscious consumers and sugar confectionery: Present aspects and projections - Konar, Nevzat; Gunes, Recep; Palabiyik, Ibrahim; Toker, Omer Said (ELSEVIER SCIENCE LONDON, 2022)
Background: The number of health conscious consumers is increasing among different socio-economic groups all over the world. The food industry and technology should be able to respond to changes in the expectations and demands of this consumer group. Therefore, preparations should be made for adaptation to the current period and possible future scenarios in all areas that concern human life. In this regard, in addition to novel food production and safety studies, any action to be taken in terms of the effects of this consumer attitude on consumption behavior is of great importance.Scope and approach: In this study, the status of confectionery technology during the rising of health conscious consumers, its effects on confectionery consumption, and priority study issues for the healthy and functional products were discussed. Within this scope, we aimed to present projections to the industry and researchers in this field by reviewing and discussing the findings of existing studies considering healthy and functional sugar confectionery products.Key findings and conclusions: Despite the high calorie concern, no significant decreases are expected in the consumption of confectionery products. Because these foods can contribute to the high mood level that consumers need. However, the acceleration gained by the increase in consumers' preference and demand for healthy foods will be effective and determinant in the future periods for sugar confectionery products. This will encourage efforts to develop functional confectionery, particularly those associated with the immune system will be of greater importance. Therefore, innovative approaches and designs are needed for confectionery products in terms of shelf life, stability, packaging and labeling. We may suggest that all stakeholders attach importance to the development of multi-functional and low-calorie products, with a package design and size suitable for on-line sales channels by considering the rising of individual consuming behavior.
Keywords: Confectionery; Consumer; Functional food; Health conscious; FOOD COLORANTS; MILK CHOCOLATE; HEDONIC HUNGER; AROMA RELEASE; CONSUMPTION; CANDIES; TEXTURE; MICROPARTICLES; FORTIFICATION; OPPORTUNITIES; Food Science & Technology